Proposal for media literacy through professional fact checking in Latin America - Ferreras Rodríguez, Eva Mª (2025)
Disinformation is an increasingly sophisticated (Frau-Meigs 2022) and normalized phenomenon in the digital ecosystem, which makes it urgent to implement solutions that strengthen the resilience of audiences. Media literacy and verification are the responses that have received the most impetus and the relationship between the two disciplines has become closer (Frau-Meigs 2022). Digital literacy has shifted to an interpretative approach as an essential tool to counter misinformation (Sábada and Salaverría 2023; Roozenbeek et al., 2022). While the activity of fact checkers has been consolidated and in recent years many fact checkers have implemented literacy as part of their professional activities, some academic circles refer to them as ‘second generation’ fact checking organizations (Çömlekçi, 2022). We understand that this is a trend and from this perspective, we propose an exploratory study on the literacy programs offered by the fact checkers that are part of the Latin American network Latamchequea. It is approached using a mixed methodology: content analysis and semi-structured interviews with the professionals. The interpretation of the results leads us to consider the degree of professionalization of the educational programs examined.